[N⋅⋅⋅I+⋅⋅⋅N] Halogen‐Bonded Dimeric Capsules from Tetrakis(3‐pyridyl)ethylene Cavitands. Issue 45 (6th October 2016) - Turunen, Lotta; Warzok, Ulrike; Puttreddy, Rakesh; Beyeh, Ngong Kodiah; Schalley, Christoph A.; Rissanen, Kari
Abstract: Two [N⋅⋅⋅I + ⋅⋅⋅N] halogen‐bonded dimeric capsules using tetrakis(3‐pyridyl)ethylene cavitands with different lower rim alkyl chains are synthesized and analyzed in solution and the gas phase. These first examples of symmetrical dimeric capsules making use of the iodonium ion (I + ) as the main connecting module are characterized by 1 H NMR spectroscopy, diffusion ordered NMR spectroscopy (DOSY), electrospray ionization mass spectrometry (ESI‐MS), and ion mobility‐mass spectrometry (TW‐IMS) experiments. The synthesis and effective halogen‐bonded dimerization proceeds through analogous dimeric capsules with [N⋅⋅⋅Ag + ⋅⋅⋅N] binding motifs as the intermediates as evidenced by the X‐ray structures of (CH2 Cl2 )2 @[3 a 2 ⋅Ag4 ⋅(H2 O)2 ⋅OTs4 ] and (CH2 Cl2 )2 @[3 a 2 ⋅Ag4 ⋅(H2 O)4 ⋅OTs4 ], two structurally different capsules. Abstract : I move in : A tetrakis(3‐pyridyl)ethylene cavitand reacts with silver tosylate forming a dimeric capsule through four [N⋅⋅⋅Ag + ⋅⋅⋅N] coordination bonds. Treatment of this Ag‐capsule with I2 leads, via precipitation of AgI, to the corresponding [N⋅⋅⋅I + ⋅⋅⋅N] halogen‐bonded capsule.